ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PENGANGGARAN BERBASIS KINERJA DI KOTA BANDA ACEH - Roza Maulina; Syukriy Abdullah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This research aims to empirically examine the influence of leadership, human resources, monitoring and evaluation, and regulation regarding the implementation of performance-based budgeting in the Banda Aceh city. Sampling was done with the purposive sampling analysis method the used is multiple linear regression using SPSS 22. This analysis data show there are significantly effect on leadership, human resoutces, monitoring and evaluation, and regulation to implementation of performance based-bugeting in the Banda Aceh city. In partial leadership, human resoutces, monitoring and evaluasi, and regulation do not significantly affect the implementation performance based-budget